Thermal conductivity of two-dimensional group IV-element thermocrystals. (December 2021) - Xu, Kaiyuan; Umar, Azka; Jiang, Chun
Abstract: A thermocrystal is a type of periodic structure bandgap material that can control heat flux transmission and reflection. In this paper, we use and improve a model based on the kinetic theory of transport processes to calculate the corresponding thermal spectra, dispersion relations and thermal transmission losses of two-dimensional thermocrystals with different film thicknesses, different lattice parameters, different modes, and linear defect structure. The results show that the thermal conduction can be reduced by approximately 19.6% using bandgap materials.